2017
DOI: 10.1515/cclm-2016-0705
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between procalcitonin and C-reactive protein in predicting bacteremias and confounding factors: a case-control study

Abstract: The elevation of CRP and PCT were significantly associated with bacteremias. PCT was superior to CRP as a diagnostic indicator for predicting bacteremias, for discriminating bacterial from nonbacterial infections, and for determining bacterial species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 24 publications
3
16
1
6
Order By: Relevance
“…Disease Markers results failed to identify a significant difference between East Asian and European population [22,23]. In our subgroup analysis, we failed to get exact age and sex information from some of the studies, which hindered the analytical process going further [21,26,31,33,36,37,40,41,54]. Our results assessing the performance of different PCT assays were in line with previous studies which demonstrated equivalence among 3 different PCT assays (Kryptor, Vidas, or Elecsys/-Cobas), as the threshold and accuracy were suggested consistent across these three tests in our study [55,56].…”
mentioning
confidence: 83%
“…Disease Markers results failed to identify a significant difference between East Asian and European population [22,23]. In our subgroup analysis, we failed to get exact age and sex information from some of the studies, which hindered the analytical process going further [21,26,31,33,36,37,40,41,54]. Our results assessing the performance of different PCT assays were in line with previous studies which demonstrated equivalence among 3 different PCT assays (Kryptor, Vidas, or Elecsys/-Cobas), as the threshold and accuracy were suggested consistent across these three tests in our study [55,56].…”
mentioning
confidence: 83%
“…Procalcitonin (PCT), a precursor hormone of calcitonin, may be secreted by different cells in multiple organs when the body is stimulated by an inflammatory response, especially bacterial infection (Nishikura, 1999 ; Linscheid et al, 2003 ). Many studies have shown that PCT has an excellent predictive ability for sepsis (Arora et al, 2017 ; Nishikawa et al, 2017 ) and increased PCT is indicative of a risk of bacteremia in patients with acute fever (Kim et al, 2011 ). Notably, in hantavirus infections, an increased serum PCT level has been found in patients with acute nephropathia epidemica (NE) caused by Puumala virus (Jereb et al, 2011 ) although no association between PCT levels and severity of disease was observed (Latus et al, 2015a ).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that when the body is stimulated by an inflammatory response, especially bacterial infection, different cells in multiple organs secrete procalcitonin ( Linscheid et al, 2003 ; Nishikura, 1999 ). Many studies have shown that procalcitonin has an excellent predictive ability for sepsis ( Arora et al, 2017 ; Kibe, Adams & Barlow, 2011 ; Nishikawa et al, 2017 ). Additionally, another study showed that there is a risk of bacteremia in patients with acute fever when the procalcitonin level is greater than 0.5 ng/ml ( Kim et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%